Dectin-1 Controls TSLP-Induced Th2 Response by Regulating STAT3, STAT6, and p50-RelB Activities in Dendritic Cells - Gu, Chao; Upchurch, Katherine; Horton, Joshua; Wiest, Mathew; Zurawski, Sandra; Millard, Mark; Kane, Robert R.; Joo, HyeMee; Miller, Lisa A.; Oh, SangKon (Frontiers in Immunology, 2021)
The epithelium-associated cytokine thymic stromal lymphopoietin (TSLP) can induce OX40L and CCL17 expression by myeloid dendritic cells (mDCs), which contributes to aberrant Th2-type immune responses. Herein, we report that such TSLP-induced Th2-type immune response can be effectively controlled by Dectin-1, a C-type lectin receptor expressed by mDCs. Dectin-1 stimulation induced STAT3 activation and decreased the transcriptional activity of p50-RelB, both of which resulted in reduced OX40L expression on TSLP-activated mDCs. Dectin-1 stimulation also suppressed TSLP-induced STAT6 activation, resulting in decreased expression of the Th2 chemoattractant CCL17. We further demonstrated that Dectin-1 activation was capable of suppressing ragweed allergen (Amb a 1)-specific Th2-type T cell response in allergy patients ex vivo and house dust mite allergen (Der p 1)-specific IgE response in non-human primates in vivo. Collectively, this study provides a molecular explanation of Dectin-1-mediated suppression of Th2-type inflammatory responses and suggests Dectin-1 as a target for controlling Th2-type inflammation.